2021
DOI: 10.1186/s12903-021-01521-3
|View full text |Cite
|
Sign up to set email alerts
|

Oro-facial malignancy in north of Iraq: a retrospective study of biopsied cases

Abstract: Background Identifying the prevalence of orofacial malignancies is essential to provide health-care programs and services for a specific population. This study aimed to specify the prevalence, clinical and histopathological features of oral malignancies in Sulaimani for over 12 years. Methods All archived reports for orofacial specimens from 2008 to 2019 were collected from three major centers in Sulaimani governorate. The demographic data, date, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…A few previous studies showed that cancer was the most common nding is oral specimens [1,4,18,[23][24]. Malignant tumors constituted 10% of specimens in our series, which is close to what was reported in Libya (8%), UAE (14.9%) and Iraq (14.5%) but higher than Kuwait (3.6%), Spain (3.9%) and UK (5.4%) [6, [23][24][25][26]. In contrast, a few studies showed that malignancy was the dominant disease among oral biopsies [27,28].…”
Section: Discussionsupporting
confidence: 88%
“…A few previous studies showed that cancer was the most common nding is oral specimens [1,4,18,[23][24]. Malignant tumors constituted 10% of specimens in our series, which is close to what was reported in Libya (8%), UAE (14.9%) and Iraq (14.5%) but higher than Kuwait (3.6%), Spain (3.9%) and UK (5.4%) [6, [23][24][25][26]. In contrast, a few studies showed that malignancy was the dominant disease among oral biopsies [27,28].…”
Section: Discussionsupporting
confidence: 88%
“…A few previous studies showed that cancer was the most common finding in oral specimens [1,4,18,[24][25]. Malignant tumors constituted 10% of the specimens in our series, which is close to what was reported in Libya (8%), the UAE (14.9%) and Iraq (14.5%) but higher than in Kuwait (3.6%), Spain (3.9%) and the UK (5.4%) [6,[24][25][26][27]. In contrast, a few studies showed that malignancy was the dominant disease among oral biopsies [28][29].…”
Section: Discussionsupporting
confidence: 88%
“…[ 40 41 42 43 44 45 ] A recent study from Iraq reported over 12 years that there was a upsurge in the oral malignancies in Sulaimani city, north of Iraq; they were predominated in males older patients. [ 47 ] Further, a study concluded that relatively higher rates of oral and oropharyngeal cancers were found among the people of GCC countries with some sorts of diversity among GCC countries. [ 48 ] Recently, the Saudi Cancer Registry identified (during 1994 and 2015) 172,424 cancer patients in Saudi Arabia.…”
Section: Methodsmentioning
confidence: 99%